Faktor-Faktor yang Mempengaruhi Daya Saing Komoditas Kopi Indonesia di Pasar Dunia - Santri, Ayu; Padapi, Astrini; Haryono, Iranita (LP3M Universitas Putra Bangsa, 2024)
As time goes by, globalization will give rise to increasingly fierce competition, so that only countries that have strong competitiveness will be able to survive, so it requires coffee producers in Indonesia to be able to meet consumer needs in a more satisfying way than in competing countries. This research aims to find out the factors that influence the competitiveness of Indonesian coffee commodities in the world market. The method used is a quantitative method using secondary data. The data analysis technique uses Multiple Linear Regression Analysis. The research results show that in the partial t test results the Production Variable (X1) has a significant effect on Export Volume (Y) and the Price Variable (X2) and the Dollar Exchange Rate Variable (X3) do not have a significant effect on Export Volume (Y) on commodity competitiveness Indonesian coffee on the world market. From the simultaneous f test results, it was found that all independent variables (X) had a significant influence on Export Volume (Y) on the competitiveness of Indonesian coffee commodities in the world market. The conclusion of this research is to increase coffee production and improve quality in order to be able to increase Indonesian coffee commodities so that they can have a higher influence on the world market.